Current‐Induced Reversible Split of Elliptically Distorted Skyrmions in Geometrically Confined Fe3Sn2 Nanotrack. Issue 9 (22nd January 2023) - Hou, Zhipeng; Wang, Qingping; Zhang, Qiang; Zhang, Senfu; Zhang, Chenhui; Zhou, Guofu; Gao, Xingsen; Zhao, Guoping; Zhang, Xixiang; Wang, Wenhong; Liu, Junming
Abstract: Skyrmions are swirling spin textures with topological characters promising for future spintronic applications. Skyrmionic devices typically rely on the electrical manipulation of skyrmions with a circular shape. However, manipulating elliptically distorted skyrmions can lead to numerous exotic magneto‐electrical functions distinct from those of conventional circular skyrmions, significantly broadening the capability to design innovative spintronic devices. Despite the promising potential, its experimental realization so far remains elusive. In this study, the current‐driven dynamics of the elliptically distorted skyrmions in geometrically confined magnet Fe3 Sn2 is experimentally explored. This study finds that the elliptical skyrmions can reversibly split into smaller‐sized circular skyrmions at a current density of 3.8 × 10 10 A m −2 with the current injected along their minor axis. Combined experiments with micromagnetic simulations reveal that this dynamic behavior originates from a delicate interplay of the spin‐transfer torque, geometrical confinement, and pinning effect, and strongly depends on the ratio of the major axis to the minor axis of the elliptical skyrmions. The results indicate that the morphology is a new degree of freedom for manipulating the current‐driven dynamics of skyrmions, providing a compelling route for the future development of spintronic devices. Abstract : Current‐driven split and integration of the elliptically distorted skyrmions are realized. At a current density of 3.8 × 10 10  A m −2, the elliptical skyrmions split into two circular skyrmions. More importantly, such a transition is reversible, which is beneficial for memory applications. The results establish a viable approach to manipulating skyrmions, significantly broadening the design of skyrmion‐based devices.